Operation level agreements : a complete guide - 2019 edition : practical toos for self-assessment - Blokdijk, Gerard (Unidentified 5STARCooks, 2018)
A professional technical roadmap to IT Operation Level Management & Agreements, operation Design & Continual operation Improvement with design, role & responsibility, KPI, communication plan & OLA template resources for organizational implementation.
Includes index.
oif 23/01/2020
Loans
Keywords: Sevice industries--Cost control; Service industries--Quality control; Operation-level agreements; Total quality management